Relationship between mental toughness level and intermittent performance among Negeri Sembilan Youth's Football Players / Mohamad Farid Haikal Othman - Othman, Mohamad Farid Haikal (2019)
This study was conducted to identify the relationship between mental toughness level and intermittent performance among Negeri Sembilan Youth's Football Players. The numbers of samples for this study are 23 youth football players who were registered by Negeri Sembilan Football Association. Spo11 Mental Toughness Questionnaire (SMTQ; Sheard 2009) that consist 14 items was used to measure the level of mental toughness and intennittent performance by using demographic profile. The data of this study was analysed by Chi¬ Square test analysis using statistical package for social science (SPSS) version 21. Overall finding for this finding is there are no significant relationship between level of mental toughness and intermittent performance among Negeri Sembilan Youth's Football Players.